Pelanggaran Hak Cipta Buku yang Diperjualbelikan Melalui E-Commerce di Kota Medan - M. Citra Ramadhan; Yadi, Pitra; Yanni Dewi Siregar, Fitri; Lubis, Muhammad Koginta (Talenta Publisher, Universitas Sumatera Utara, 2023)
This study aims to obtain a comprehensive overview of the legal provisions related to the legal regulation of book copyright, forms of copyright infringement of books traded through e-commerce in Medan City, and the causes of copyright infringement of books traded through e-commerce. In line with the purpose of this study, the research method used is normative legal research, in order to get a full picture not only of the positive law that regulates it (law in a book), but also the consequences of its enforcement in society (law in action). The results of this study indicate that books are copyrighted works protected by Law Number 28 of 2014 concerning Copyright, so that the creator gets legal protection from all forms of infringement, both with respect to moral rights and economic rights. Forms of copyright infringement in the form of infringement of economic rights, where books traded through e-commerce in Medan is a book of the results of the copy without the right or permission of the creator or copyright holder; Copyright infringement of books traded through e-commerce can occur because of the weak copyright law system both in terms of substance, structure and culture of society itself.